Pendayagunaan Wakaf Tunai dan Dampaknya terhadap Kesejahteraan Masyarakat - Matangaji, Amaludin (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2025)
This study aims to answer how the role and implementation of the waqf to increase in the public welfare. Research approach is qualitative approach explanatory. Data collection of documentation, interviews and direct observation as well as the strategy is a case study. Techniques of analysis is descriptive narrative analysis techniques and pairing pattern. The key informant was led of El-azam Boarding school and supporter informants are the recipients of empowerment. The results showed that the keys to success in the role and implementation waqf empowerment to increase social welfare is; First, the successful establishment of fund-raising by type of particular quality concept. Second, success in empowerment Cash waqf financing. Third, allocation the profit and advantage of cash waqf has a significant to increase the public welfare. The execute through money-run Waqf economical and professional management have a greater impact on the improvement of social welfare compared to waqf immovable assets.